Constructability practice and project delivery processes in the Nigerian construction industry - Akpan, E.O.P.; Amade, B.; Okangba, S.E.; Ekweozor, C.O. (Penerbit UKM, 2014)
As projects are getting complex by the day and for the fact that project failures – project abandonment, collapsed structures are constant discourse in the Nigerian news media, the need for constructability becomes very crucial in order to achieve project success. This study is aimed at investigating and analyzing the implementation of constructability in project delivery process in the Nigerian construction industry using Rivers State, Nigeria as a case study. Data was collected through questionnaire and interview approach. Results of data analyzed revealed that although a high percentage of the sampled population are familiar with the term “constructability”, nearly all do not have corporate constructability implementation manual nor apply formal constructability implementation programs and techniques as obtained in more developed countries. Constructability implementation is therefore neither systematic nor comprehensive in virtually all the firms surveyed. The universal principles of constructability were accepted by the professionals and rated in the order of importance. The most critical was identified as the carrying out of thorough investigation of site and development of a project plan. Conditions that constrain constructability in the opinion of the professionals were also identified and rated in the order of impact. Spearman rank correlation analysis revealed an agreement of opinion between different respondent groups in the sampled population. Engineers, project managers and other industry practitioners are enjoined to adopt these principles in their planning, design and construction activities in order to improve the overall project performance and achieve best practices in the industry.